EXPLOITATION OF THE EARTH REPRESENTED IN MOANA AND ITS RELEVANCE TO CURRENT ENVIRONMENTAL ISSUES: AN ECOFEMINISM STUDY - R. Hariyani Susanti; Vera Sardila; Herlinda Herlinda; Welli Marlisa; Aramudin Aramudin (Lire Journal (Journal of Linguistics and Literature), 2022)
The issue of gender inequality and environmental, such as flooding, has recently become increasingly happened and discussed in the mass media. Both issues are well represented in the animated film Moana. There are many symbols in the animated film that can be related to both ecological theory and feminism. However, by using an ecofeminism approach, the author tries to analyze the symbols and codes that represent the exploitation of marginal parties in the film. From the results of the analysis, it was found that there are many representations related to the exploitation of women and the environment found in the film and this is relevant to the issue of equality and environmental issues today.